The evolutionary dynamics of plastic foraging and its ecological consequences: a resource-consumer model - Ledru, Léo; Garnier, Jimmy; Guillot, Océane; Faou, Erwan; Noûs, Camille; Ibanez, Sébastien (Peer Community Journal, 2023)

(untitled)
Phenotypic plasticity has important ecological and evolutionary consequences. In particular, behavioural phenotypic plasticity such as plastic foraging (PF) by consumers, may enhance community stability. Yet little is known about the ecological conditions that favor the evolution of PF, and how the evolutionary dynamics of PF may modulate its effects on community stability. In order to address these questions, we constructed an eco-evolutionary model in which resource and consumer niche traits underwent evolutionary diversification. Consumers could either forage randomly, only as a function of resources abundance, or plastically, as a function of resource abundance, suitability and consumption by competitors. PF evolved when the niche breadth of consumers with respect to resource use was large enough and when the ecological conditions allowed substantial functional diversification. In turn, PF promoted further diversification of the niche traits in both guilds. This suggests that phenotypic plasticity can influence the evolutionary dynamics at the community-level. Faced with a sudden environmental change, PF promoted community stability directly and also indirectly through its effects on functional diversity. However, other disturbances such as persistent environmental change and increases in mortality, caused the evolutionary regression of the PF behaviour, due to its costs. The causal relationships between PF, community stability and diversity are therefore intricate, and their outcome depends on the nature of the environmental disturbance, in contrast to simpler models claiming a direct positive relationship between PF and stability.